Sandfish (Holuthuria scabra) Fisheries in Saleh Bay: Stock Status Based on Fishermen’s Perception and Catches [Perikanan Teripang Pesisir (Holuthuria scabra) Teluk Saleh: Status Stok berdasarkan Persepsi Nelayan dan Hasil Tangkapan] - Neri Kautsari; Etty Riani; Djamar TF Lumbanbatu; Sigid Hariyadi (Jurnal Ilmiah Perikanan dan Kelautan, 2019)
Abstract The exploitation of sandfish (Holuthuria scabra) in Saleh Bay is so far not well managed. Consequently, over-fishing and species extinction of sea cucumbers emerge. Currently, information related to the supply of sandfish (H. scabra) is very limited. The purpose of this research was to investigate the stock status of sandfish (H. scabra) based on the fishermen’s perception and fish capture information. This research was carried out in the Saleh Bay coast, Sumbawa District, West Nusa Tenggara. The method used was a semi-closed interviews with the scope of fishermen’s demography, methods, efforts and catches, and fishermen’s perception of the stock condition, conducted by a total of 39 respondents. The result of this research showed that sea cucumber fishermen consisted of male and female with a ratio of 46 : 54, age ranged between 26-59 years old, all were married; education level between unschooled to senior high school; fishermen were from Bajo tribe (37%), Bugis (25%), Samawa (5%) and Mandar (33%). Sea cucumbers were caught by hands for 5-6 weeks (1-4 hours per day), CPUE ranges between 2 to 25 kg (wet weight). The main reason for capturing sea cucumber was because of the ease of method (97%). 84% of the fishermen stated that sea cucumber stock in Saleh Bay declined. The research cocluded the fishermen on Saleh Bay assumed that sandfish (H. scabra) had decreased in stock.